(untitled) (Global Journal of Management and Business Research, 2020)
The Balanced Scorecard BSC first created by Kaplan and Norton in 1992 has been developed over the last 28 years gaining attention all over the world In Ethiopia context ministry of civil service in 2010 The introduction of Civil Service Reform program CSRP as part of the 14 national capacity building programs was in response to weaknesses in the organizational structure and the public service delivery and to simulate the overall development effort of the country